Transboundary river basin organizations in Africa: assessing the secretariat - Saruchera, Davison; Lautze, Jonathan F. (IWA Publishing, 2016)
Secretariats are an increasingly common feature in Africa’s transboundary river basin organizations (RBOs). Non-secretariat-based forms of transboundary RBOs nonetheless also exist, and such forms of cooperation have often functioned effectively. These realities drive questions about the rationale and role for secretariats. This paper employs two approaches to compare secretariat-based RBOs vis-à-vis RBOs without secretariats in Africa. First, we compared the degree to which five governance instruments, determined to enable effective transboundary water management, are contained in treaties creating secretariat-based RBOs versus treaties creating non-secretariat-based RBOs. Second, the costs and benefits of six African transboundary RBOs – three with secretariat and three without – were compared based on a survey of regular costs and volume and number of projects. Key findings are that RBOs with secretariats have achieved stronger governance and secured more investment than RBOs without secretariats. Costs associated with operating secretariats appear justified by their benefits. These findings help to lay an improved basis for selecting desired models of RBOs in Africa’s transboundary basins.